(untitled) (Nucleus, 2023)
Soil penetration resistance is an important indicator of soil compaction. Knowing the precise location of layers with increased resistance to penetration can aid in the mechanical management of soil. In this context, the objective of this study was to analyze the soil penetration resistance of a Dystroferric Red Latosol, under no-tillage system with additional compaction due to tractor traffic, using multivariate factor analysis. Compaction states were induced with tractor traffic in a no-tillage area in 0, 2, 4, 6, 8, and 12 passes of an agricultural tractor. An electronic penetrometer was used to evaluate the soil resistance, with 10 points being taken in each experimental plot. Simultaneously, deformed structure samples were collected to determine soil moisture. Multivariate factor analysis was used as a tool to analyze soil penetration resistance, seeking to determine its stratification up to 0.40 m depth. Factor analysis applied to the study of soil with different tractor traffic intensities allows the identification of layers of growth, transition, reduction, and stabilization of soil resistance to penetration at depth. Soil layers associated with management with furrows in previous crops were identified, as well as compacted surface soil layers induced by tractor traffic compaction, in addition to layers with stabilization at depth, possibly associated with pedogenetic factors.